A novel approach to study polymorphism of microsatellite loci in humans - Lo, Samuel Tat Ming (2013)
Short tandem repeats (STRs) or microsatellite DNA are blocks of tandem repeat units of 1 to 6 base pairs (bp) that are ubiquitous, abundant, and highly polymorphic in eukaryotic genomes. Due to their highly polymorphic nature, they are used as markers for human identity testing, disease diagnostics, and genetic mapping studies. One example is the study of polymorphisms in the non-recombining portion of the Y chromosome for detecting male-mediated migration events and for reconstructing paternal history. As such, Y-linked polymorphic short tandem repeats (STRs) which consist of reiterated GATA and CA units, have been studied. Conventional methods for genotyping of STRs includes the less sensitive restriction fragment length polymorphism (RFLP) and low-throughput pulsed field gel electrophoresis (PFGE). This involves electrophoretic separation of fluorescently labelled PCR products in denaturing gels for allele sizing. Although such methods are performed with reasonable accuracy on a routine basis, the preparation and running of gels is a time and labor-intensive process. Thus, in the present study, we aimed to analyze Y-specific poly(CA/GT)n designated YCAI, YCAII, and YCAIII (early reported regions) and a new CA repeat region YCAIV selected by NCBI Y-chromosome database analysis by “etandem” software using a novel approach of PCR-matrix assisted laser desorption/ionization- time-of-flight mass spectrometry (MALDI-TOF MS). [1st Award]